2015
DOI: 10.1007/s00068-015-0508-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinician-performed abdominal sonography

Abstract: Clinician performed point-of-care sonography is particularly well suited to abdominal applications. Future investigations may further confirm and extend its utility at the bedside.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 58 publications
0
11
0
1
Order By: Relevance
“…Abdominal POCUS can be used to readily identify a variety of pathological states including ascites, cholecystitis, cholelithiasis, nephrolithiasis, hydronephrosis, and abdominal aortic aneurysm. [54][55][56] Its use has been shown to improve diagnostic accuracy and reduce ER length of stay. 55,56 While abdominal POCUS is incorporated into standardized examinations such as the Focused Assessment with Sonography for Trauma (FAST), these examinations are subject to variability based on user experience and have not been extensively validated as tools to assess competency.…”
Section: Abdominal Pocusmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdominal POCUS can be used to readily identify a variety of pathological states including ascites, cholecystitis, cholelithiasis, nephrolithiasis, hydronephrosis, and abdominal aortic aneurysm. [54][55][56] Its use has been shown to improve diagnostic accuracy and reduce ER length of stay. 55,56 While abdominal POCUS is incorporated into standardized examinations such as the Focused Assessment with Sonography for Trauma (FAST), these examinations are subject to variability based on user experience and have not been extensively validated as tools to assess competency.…”
Section: Abdominal Pocusmentioning
confidence: 99%
“…[54][55][56] Its use has been shown to improve diagnostic accuracy and reduce ER length of stay. 55,56 While abdominal POCUS is incorporated into standardized examinations such as the Focused Assessment with Sonography for Trauma (FAST), these examinations are subject to variability based on user experience and have not been extensively validated as tools to assess competency. 24,57 The Objective Structured Assessment of Ultrasound Skills (OSAUS) was developed through expert consensus and includes elements that assess knowledge acquisition, knowledge application, technical competence, and integration into clinical practice (Table 4).…”
Section: Abdominal Pocusmentioning
confidence: 99%
“…Because of the disagreement between the sonographic criteria needed to diagnose SBO, Dickman et al noted that while identifying dilated bowel loops is essential, there is an increased likelihood for diagnostic accuracy when there is also abnormal peristalsis. This study also reported that sonography has the potential to be used as an alternative method to identify SBO [ 15 ]. Dickman et al recommended the use of ultrasounds at the bedside given the lack of ionizing radiation, the decreased length of stay for the patient, and the ease of use of POCUS in crowded EDs [ 15 ].…”
Section: Accuracy Of Ultrasound In Small Bowel Obstructionmentioning
confidence: 99%
“…This study also reported that sonography has the potential to be used as an alternative method to identify SBO [ 15 ]. Dickman et al recommended the use of ultrasounds at the bedside given the lack of ionizing radiation, the decreased length of stay for the patient, and the ease of use of POCUS in crowded EDs [ 15 ].…”
Section: Accuracy Of Ultrasound In Small Bowel Obstructionmentioning
confidence: 99%
“…There is a growing interest in assessing optic nerve sheath diameter (ONSD) to detect elevated intracranial pressure (ICP) and inferior vena cava diameter to predict intravascular volume, endotracheal tube placement verification in relation to glottis, and cardiopulmonary resuscitation. [3][4][5][6][7][8] The most important advantages of POCUS are being easy to use, repeatable, noninvasive, cheap, painless, and radiation-free. 1 In recent years, most PICUs have acquired POCUS technology, and the training courses for pediatric emergency and intensive care specialists have become popular.…”
Section: Introductionmentioning
confidence: 99%